Teaching Arabic to the Indonesian Student from a Functional Perspecive/تعليم اللغة العربية للدارس الإندونيسيي من منظور وظيفي - Manshur, Umar (JURNAL IJ-ATL, 2017)
Learning Arabic in Indonesia recently is more oriented on comprehension syintax and morphology which aims at reading skill on islamic classic book. However in modern challenge, indonesian learner are requaired able to communicate in Arabic actively, so learning Arabic is not only focused on the development of receptive skill, but on productive skill as well. Learning Arabic on the development of productive skill does not only use communicative method, moreover it is also conducted for functional material, including the grammar which is learned functional grammar.كان تعليم اللغة العربية في إندونيسيا يهدف إلى تعزيز القواعد النحوية والصرفية لأجل تنمية المهارة في قراءة الكتب التراثية. إلا أن تحديات معاصرة تتطلب الدارس الإندويسي أن يتقن الاتصال النشيط باللغة العربية، فينبغي تعليمها لا يهدف إلى تنمية المهارة الإستقبالية فقط، بل يهدف أيضا إلى تنمية المهارة الإنتاجية. وتعليم اللغة العربية الذي يهدف إلى تنمية المهارة الإنتاجية لا يكفي باستخدام الطريقة الإتصالية فحسب، بل لا بد أن تكون المواد المحضرة موادا وظيفية وكذلك القواعد اللغوية المتعلمة أن تكون قواعدا وظيفية.